Harnessing the Power of Yoga: An Integrative Review on Anxiety Management - Thakar, Nivedita; Jani, Sumeet; Panchal, Dinesh (International Research Journal of Ayurveda & Yoga, 2024)
Yoga has emerged as a new approach as a favorable adjunctive therapy in the management of anxiety disorders, offering a complete approach that integrates physical postures (asanas), breathing techniques (pranayama), and meditation practices (Dhyana). This integrative review synthesizes current research findings to explore the efficiency of yoga in alleviating signs of anxiety. By examining a range of studies, including randomized controlled trials, with control observational research, and data analyses, this review evaluates the mechanisms through which yoga influences anxiety levels, such as stress reduction, modulation of physiological responses, and enhancement of emotional regulation. In addition, the review discusses practical implications for health-care practitioners, highlighting yoga’s potential as a safe and accessible intervention for anxiety management across diverse populations. Moreover, it identifies gaps in current research and proposes directions for future studies to further elucidate yoga’s role in promoting mental well-being. Ultimately, this review underscores the therapeutic potential of yoga as a corresponding approach in the comprehensive treatment of anxiety disorders. Anxiety disorders are among the most numerous mental health conditions worldwide, affecting individuals of all ages and backgrounds, for all ages people, In a recent study, most of the anxiety are affected on young generation. While conventional treatments such as medication and psychotherapy remain cornerstone approaches, complementary and alternative interventions, including yoga, offer promising adjunctive options. This review aims to critically evaluate the existing literature on the use of yoga for anxiety and provide insights into its clinical application and potential mechanisms of action.[1] Anxiety disorders show a significant public health concern, affecting millions worldwide with profound impacts on daily functioning and quality of life (QoL). According to the World Health Organization (WHO), anxiety disorders are among the most rampant mental health disorders globally, contributing to a substantial burden of disability-adjusted life years (WHO, 2017). The hallmark of anxiety disorders is excessive worry, fear, and physiological arousal in response to perceived threats or stressful situations, often leading to avoidance behaviors that can